1841. Implementation of an Outpatient Antimicrobial Stewardship Program to Reduce Fluoroquinolone Overprescribing at a Veterans Affairs Medical Center (VAMC). (26th November 2018) - Pilate, Marcy; Hunter, Andrew; Ashong, Chester; Sofjan, Amelia; Trautner, Barbara W; Rodriguez-Barradas, Maria C; Garey, Kevin
Abstract: Background: Fluoroquinolones are often overprescribed in outpatient settings; however, stewardship programs designed to prevent overuse are not well described. The primary purpose of this study was to evaluate the change in overall and appropriate fluoroquinolone prescribing rates by primary care providers within internal medicine primary care clinics at the Houston VAMC before and after implementation of an audit and feedback intervention. Methods: All fluoroquinolone prescriptions written by internal medicine primary care providers were included in this study. A medical chart audit to assess the appropriateness of fluoroquinolone prescriptions was conducted, and face to face feedback was given to providers regarding prescribing patterns. Aggregate monthly fluoroquinolone utilization data were also provided. Monthly face to face academic detailing sessions were provided regarding the treatment of common outpatient infectious diseases, appropriate fluoroquinolone use, and suggested alternatives. Study objectives were assessed before and after the intervention time period using segmented regression time series analysis including non-intervention internal medicine primary care comparator clinics. Results: In the intervention clinics, rates of fluoroquinolone orders decreased from 9.4 ± 5.8 orders per week per 1, 000 patient visits in the pre-intervention time period to 6.9 ± 6.6 orders per week per 1, 000 patient visits in the post-intervention time periods. Using segmented regression analysis, controlling for change in prescribing rates in the non-intervention clinics, and changes in the rate of prescribing over time, the intervention was associated with a 3.1 ± 0.99 decrease in fluoroquinolone orders per week per 1, 000 patient visits ( P = 0.0019). The percentage of orders deemed appropriate increased from 50 ± 31% in the pre-intervention time period to 66 ± 53% in the post-intervention time period ( P = 0.06). Rates of fluoroquinolone orders did not change in the non-intervention clinics. Conclusion: An audit and feedback intervention in ambulatory care clinics was able to reduce the rate of fluoroquinolone orders and increase the percent of orders deemed appropriate. Disclosures: All authors: No reported disclosures.